The ConstructiCon: Language as a Cognitive Network of Constructions - Hilpert, Martin; Benjamin Lyngfelt; Tiago Torrent (My University, 2025)
This article is a summary introduction to the conception of language as a mental network of constructions: a constructiCon. We outline the way this notion has evolved over the history of construction grammar (CxG), from inheritance networks to association networks and deconstructionist networks. We also give an overview of the kinds of network relations that have been proposed in the literature, and address construction networks in relation to linguistic change.
Keywords: Association network; ConstructiCon; Construction; Deconstructionist network; Inheritance; Language change; Network; Network relations